MiR-124 Radiosensitizes human colorectal cancer cells by targeting PRRX1. - Yuqin Zhang; Lin Zheng; Jing Huang; Fei Gao; Xiaoshan Lin; Lian He; Dan Li; Zhijun Li; Yi Ding; Longhua Chen (PLoS ONE)
One of the challenges in the treatment of colorectal cancer patients is that these tumors show resistance to radiation. MicroRNAs (miRNAs) are involved in essential biological activities, including chemoresistance and radioresistance. Several research studies have indicated that miRNA played an important role in sensitizing cellular response to ionizing radiation (IR). In this study, we found that miR-124 was significantly down-regulated both in CRC-derived cell lines and clinical CRC samples compared with adjacent non-tumor colorectal tissues, MiR-124 could sensitize human colorectal cancer cells to IR in vitro and in vivo. We identified PRRX1, a new EMT inducer and stemness regulator as a novel direct target of miR-124 by using target prediction algorithms and luciferase assay. PRRX1 knockdown could sensitize CRC cells to IR similar to the effects caused by miR-124. Overexpression of PRRX1 in stably overexpressed-miR-124 cell lines could rescue the effects of radiosensitivity enhancement brought by miR-124. Taking these observations into consideration, we illustrated that miR-124 could increase the radiosensitivity of CRC cells by blocking the expression of PRRX1, which indicated miR-124 could act as a great therapeutic target for CRC patients.